Does the Development of Special Economic Zones Improve the Welfare of Local Communities? : An Analysis of the Development Policy of JIIPE Gresik - Iswanto, Denny (Journal of Business and Political Economy : Biannual Review of The Indonesian Economy, 2025)
This study aims to analyze the impact of the Java Integrated Industrial and Ports Estate (JIIPE) Special Economic Zone (SEZ) development policy in Gresik on community welfare, with a focus on investment, industrial downstreaming, and employment. By using a descriptive qualitative approach with secondary data analysis methods, data were obtained from policy documents, official government reports, scientific publications, and other reliable sources. The research results show that in 2023, the JIIPE Special Economic Zone (SEZ) succeeded in attracting strategic investment and encouraging industrial downstreaming, especially in the manufacturing and mineral processing sectors, with a total investment reaching IDR 31.4 trillion, making it the SEZ with the largest investment value in Indonesia. This positive impact is reflected in the increase in the Purchasing Power Index of the Gresik community and the decline in poverty rates. However, local labor absorption still shows a significant gap, reaching only 45% compared to the regional target of 60%. This condition reflects various challenges, such as competency mismatches, shifts in local economic structures, limited vocational education, and a lack of integrated labor market information. Furthermore, economic benefits have not been distributed evenly, marked by changes in traditional livelihoods and potential environmental impacts. Therefore, regional policy integration is needed, accompanied by increased human resource capacity, MSME empowerment, participatory governance, socioeconomic impact mitigation, and strict environmental monitoring so that the benefits of SEZs can be felt in an inclusive and sustainable manner. Keywords: Socio-Economic Impact; Special Economic Zones; investment; industrial downstreaming; employment. JEL: R11, R58, E14, J21